Phylogeny, biogeography and classification of Teletisoptera (Blattaria: Isoptera). (29th April 2022) - Wang, Menglin; Hellemans, Simon; Šobotník, Jan; Arora, Jigyasa; Buček, Aleš; Sillam‐Dussès, David; Clitheroe, Crystal; Lu, Tomer; Lo, Nathan; Engel, Michael S.; Roisin, Yves; Evans, Theodore A.; et al.
Abstract: Termites are social cockroaches distributed throughout warm temperate and tropical ecosystems. The ancestor of modern termites roamed the earth during the early Cretaceous, suggesting that both vicariance and overseas dispersal may have shaped the distribution of early diverging termites. We investigate the historical biogeography of three early diverging termite families –Stolotermitidae, Hodotermitidae and Archotermopsidae (clade Teletisoptera) – using the nuclear rRNA genes and mitochondrial genomes of 27 samples. Our analyses confirm the monophyly of Teletisoptera, with Stolotermitidae diverging from Hodotermitidae + Archotermopsidae approximately 100 Ma. Although Hodotermitidae are monophyletic, our results demonstrate the paraphyly of Archotermopsidae. Phylogenetic analyses indicate that the timing of divergence among the main lineages of Hodotermitidae + Archotermopsidae are compatible with vicariance. In the Stolotermitidae, however, the common ancestors of modern Porotermes Hagen and Stolotermes Hagen are roughly as old as 20 and 35 Ma, respectively, indicating that the presence of these genera in South America, Africa and Australia involved over‐water dispersals. Overall, our results suggest that early diverging termite lineages acquired their current distribution through a combination of over‐water dispersals and dispersal via land bridges. We clarify the classification by resolving the paraphyly of Archotermopsidae, restricting the family to Archotermopsis Desneux and Zootermopsis Emerson and elevating Hodotermopsinae ( Hodotermopsis Holmgren) as Hodotermopsidae ( status novum ). Abstract : We reconstructed time‐calibrated phylogenetic trees of Teletisoptera, including representatives of all genera sampled across their distribution range. Our results suggest that Teletisoptera acquired their distribution through a combination of over‐water dispersals and dispersal via land bridges. We resolved the paraphyly of Archotermopsidae, restricting the family to Archotermopsis Desneux and Zootermopsis Emerson and elevating Hodotermopsinae ( Hodotermopsis Holmgren) as Hodotermopsidae ( status novum ).